BAITUL MAL DAN GHANIMAH STUDI TENTANG IJTIHAD UMAR BIN KHATTAB DALAM PENGUATAN LEMBAGA KEUANGAN PUBLIK - Alimuddin, Agus; Putri, Fani Monada Essa; Atasoge, Immawan Azhar Ben; Alvia, Risa (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2022)
Economic development is a fundamental thing for the welfare of the people. Umar ibn Khattab was one of the caliphs who proved the greatness of the Islamic economic system. The constitutional institutionalization of Baitul Mal was established in the time of Umar ibn Khattab and changed and formed various departments. The research aims to know the Baitul Mal and Ghanimah as one of the instruments for strengthening public financial institutions. The research methods used by researchers are Library research. The results of his study contextualise Ijtihad Umar ibn Khattab about Baitul Mal changed. At the time of Rasulullah SAW treasure (Baitul Mal) which is the source of the state's income stored in the mosque in a short period then distributed to the community. Meanwhile, in the period of Umar ibn Khattab the treasure was kept in a long time then distributed according to the needy but also the establishment of departments according to their respective fields. Ijtihad Umar ibn Khattab on Ghanimah raises various kinds of this kind of reticeship due to many changes in establishing a law.